Inequality Effect of Metacognition and Adaptivity Skill in Science Achievement of Indonesia Students - Kusuma, Mobinta (Cakrawala: Jurnal Pendidikan, 2021)
This study aims to determine the influence of inequality in metacognition and adaptability to the achievement of science scores at the student level and school level in Indonesia. Science learning is expected to be able to develop high-level thinking skills needed in the educational process in the industrial era 4.0, including factors of metacognition ability and ability adaptation. This research is an expost facto study with a qualitative exploratory descriptive type. The data is secondary data derived from the 2018 PISA survey. Data analysis using multilevel linear models through the Jamovi 1.6.23 program. The multilevel model used consists of 3 models, namely (1) intercept model without predictor, (2) intercept model with predictor level 1 , ( 3) intercept model with predictor level1 & level 2. The results of the analysis show that model 2 is considered significant that the achievement of students' science scores is more influenced by student abilities, while the type of school does not have a contribution which is significant to the achievement of science scores.